THE CULTURAL DISPLAY OF MAULUD IN LOMBOK: HARMONIOUS INTERPLAY OF ISLAM AND LOCAL ADAT - Erni Budiwanti (Harmoni, 2017)
The birthday of Prophet Muhammad is usually celebrated not only in Islamic countries where Muslims are the majority, but in places where the Muslims are in minority. In Lombok, a small isle located to the east of Bali, the majority of the islanders, the Sasak, ritualise this important event in accordance with their own cultural tradition. This paper generally discusses on the varied contextualisation of the Prophet Muhammad birthday, called the Maulud1, and more specifically, it attempts to explain: i) how the Sasak Muslims of Lombok create and develop their own local cultural fashions to commemorate the prophet Muhammad’s birthday, ii) how they are connected to Islam, iii) and how they synchronize and the relationship between both of local customary and universal tenet of Islam as a guide to correct living. These three main issues exposing the interplay of syari’at and adat in the Maulud celebrations serve the evidence that Sasak Muslims of Lombok are not a homogenous entity. Domestificating Islam in accordance with the varied Sasak’s cultural symbols and meanings is quite prominent especially when the birth of the Prophet Muhammad is revived in jubilee. The notion of localized Islam gets stronger, and even reaches its highest tone especially when the central figure of Islam is remembered to reassert the essential role of adat as accompanying element of religion. The selected Maulud celebrations of this study is focused among Muslims living in Lingsar (West Lombok), Bayan (North Lombok), Lenek and Songak (East Lombok).